Isolation and characterization of some intracellular pigmented bacteria from soil & coal powder - Mitra, Debasis; Mondal, Arup Kumar; Acharya, Saikat; Mukhopadhyay, Arijit (Research in Biotechnology, 2014)
We have isolated some intracellular pigmented (Red, yellow, pink and orange) bacteria from West Bengal and Odisha state. It was screened for biochemical test and other remarkable works. In this study, two types of bacteria (AD2 & SOM3) isolated from coal and other two types of bacteria (ADA4 & DM5) isolated from soil sample. All bacterial strain growth on temperature was also looked into the different condition. ADA4 has highly protease activity see in CMC agar and Skimmed milk agar.